Estudo do comportamento dos parâmetros de antenas de microfita utilizando diferentes configurações de arranjos de estruturas EBG/PBG - Maia, Anamaria Sena (2016)
Communication systems it has excelled in the development, social, economic and cultural society. Every time there are new technologies seeking to offer the fastest, easy and reliable access to various communications services. In this context, the microstrip antennas stand out by having compact size and reduced cost. However, it presents some limitations related to narrow bandwidth and low gain. A significant advance to minimize these losses came to the use of structures EBG (Electromagnetic Band Gap) and PBG (Photonic Band Gap) in the components of the antennas. This paper proposes the study and analysis of the behavior of microstrip antennas properties designed with EBG/PBG structures in the substrate and the ground plane. So that the structures are arranged just under the patch and are developed with variations in radius, cylinder height and positioning in the ground plane. For the resonance frequency 5.85 GHz, and substrates of different permittivity. In computer modeling was used ANSYS HFFS® software. After analyzing the simulated results seven devices were built, through a vector network analyzer, the measurements of the main parameters were performed. Ultimately simulation are compared and measured values, so that the results presented in most configurations a concord in the pattern of graphics, although the frequency displacement. Also noted that antennas with the EBG/PBG structures presented multiband, enabling the application specific frequency bands as well as, an increase in the value of total gain, bandwidth and reduction of surface currents